Aqueous mineral carbonation of oil shale mine waste (limestone): A feasibility study to develop a CO2 capture sorbent. (15th April 2021) - Puthiya Veetil, Sanoop Kumar; Rebane, Kaarel; Yörük, Can Rüstü; Lopp, Margus; Trikkel, Andres; Hitch, Michael
Abstract: The development of a Ca-based CO2 capture sorbent from a limestone-rich mine waste via aqueous mineral carbonation was first time evaluated. Aqueous carbonation of calcined oil shale mine waste rock was conducted at the laboratory scale at ambient temperature and atmospheric gas pressure using CO2 gas mixture simulated the average exhaust gas composition of a fossil fuel power generation plant. The dissolution and carbonation of calcium were found to be optimal at 2.5% pulp density and were found to proceed faster during the initial 5–10 min. The overall aqueous carbonation efficiency was estimated at ≥89%. The carbonation process resulted in the production of pure calcite, whereas a mixture of Ca and Mg carbonates was found in the reaction residue. The CO2 uptake capacity (∼80 wt%) of the developed Ca-based sorbent was promising and revealed that it can be used for direct CO2 capture. Graphical abstract: Image 1 Highlights: A novel Ca-based CO2 capture sorbent developed from the oil shale mine waste. Oil shale mine waste is a viable applicant for aqueous mineral carbonation. Ca-conversion efficiency of 89% achieved at ambient condition. The sorbent has found to be efficient for cyclic CO2 capture (80 wt%) from flue gas.